1992
DOI: 10.1128/aem.58.8.2420-2425.1992
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Legionella pneumophila and Acanthamoeba polyphaga: physiological status and susceptibility to chemical inactivation

Abstract: Survival studies were conducted on Legionella pneumophila cells that had been grown intracellularly in Acanthamoeba polyphaga and then exposed to polyhexamethylene biguanide (PHMB), benzisothiazolone (BIT), and 5-chloro-N-methylisothiazolone (CMIT). Susceptibilities were also determined for L. pneumophila grown under iron-sufficient and iron-depleted conditions. BIT was relatively ineffective against cells grown under iron depletion; in contrast, iron-depleted conditions increased the susceptibilities of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(81 citation statements)
references
References 27 publications
(31 reference statements)
2
70
1
8
Order By: Relevance
“…It should also be noted that although we found that numbers of L. monocytogenes and S. aureus were greater in the presence of A. polyphaga these data do not compare to that obtained using this amoebal strain and L. pneumpohila serogroup 1, subtype Knoxville (Barker et al, 1992). Barker et al (1992) set up their experiments in exactly the same way as we have in our experiments, except that a MOI of 1 : 1 was used, and they found that bacterial numbers were 2-3 logs higher after 48 h of coculture than in the absence of A. polyphaga.…”
Section: Discussioncontrasting
confidence: 91%
“…It should also be noted that although we found that numbers of L. monocytogenes and S. aureus were greater in the presence of A. polyphaga these data do not compare to that obtained using this amoebal strain and L. pneumpohila serogroup 1, subtype Knoxville (Barker et al, 1992). Barker et al (1992) set up their experiments in exactly the same way as we have in our experiments, except that a MOI of 1 : 1 was used, and they found that bacterial numbers were 2-3 logs higher after 48 h of coculture than in the absence of A. polyphaga.…”
Section: Discussioncontrasting
confidence: 91%
“…Post-exponential phase bacteria which are released from a depleted host cell are short, thick, £agellated and highly motile. In addition, this phenotype is more resistant to biocides, antibiotics and it is more invasive and virulent in di¡erent infection models [21,56]. Within the reprogrammed, maturation-blocked vacuole, L. pneumophila alters its physiology and converts to a replicative form (exponential growth phase).…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…From a public health perspective, amoebae, and notably amoebal cysts, can be highly resistant to various physical and chemical stresses and can thus protect any intracellular microorganism from deleterious environmental conditions that would normally kill them (King et al, 1988;Kilvington & Price, 1990;Barker et al, 1992). This protective effect is of increasing concern because it is speculated that partially efficient biocide treatments might select for FLA together with their intracellular microorganisms.…”
Section: Introductionmentioning
confidence: 99%